Energy costs of Hannibal’s alpine crossing - Emilio Berti; Fritz Vollrath (Proceedings of the National Academy of Sciences, 2026)
Hannibal crossed the Alps with a large army containing 37 war elephants in 218 BC. Details of his route have scholars regularly debate historical reports in the light of logistical and topographical considerations. Among the possible alpine passes, the route crossing at the Col du Clapier was considered the most likely candidate. Recent philological and geomorphological analyses suggest instead a route via the Col de la Traversette. Here, we examined these options focusing on the energy costs of the crossing with an emphasis on the war elephants. Our analysis favors the route of the Traversette while also providing possible insights into Hannibal’s thinking concerning both the logistics and psychology of elephant warfare.